PEMODELAN MATEMATIKA KEKERASAN DALAM RUMAH TANGGA (KDRT) TERHADAP PEREMPUAN DI INDONESIA DENGAN MENGGUNAKAN SOLUSI NUMERIK RUNGE-KUTTA ORDE EMPAT - AULIYAK, MAMLUATUL; HASANAH, AMALIYATUL (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The high number of domestic violence cases in Indonesia indicates the need for a scientific approach to understand the dynamics of the spread and more systematic control efforts. In this study, model is developed into six compartments, namely ShIRSvHC. In the model, the equilibrium point and stability of the equilibrium point are sought, as well as numerical simulations using the fourth order Runge-Kutta method and the simulation results are compared with actual data for 2020-2024. Evaluation of model accuracy is done by calculating the relative error. The simulation results show that the sub population has decreased every time with a population of about 268,030 women. The I population experienced an increase at the beginning of the period and experienced a significant decrease in the following year, the R population experienced an increase at the beginning to the middle of the period and for the and H, C populations experienced an increase every time.